Lineage-Specific Evolutionary Histories and Regulation of Major Starch Metabolism Genes during Banana Ripening - Jourda, Cyril; Cardi, Céline; Gibert, Olivier; Giraldo Toro, Andrès; Ricci, Julien; Mbéguié-A-Mbéguié, Didier; Yahiaoui, Nabila (Frontiers in Plant Science, 2016)
Starch is the most widespread and abundant storage carbohydrate in plants. It is also a major feature of cultivated bananas as it accumulates to large amounts during banana fruit development before almost complete conversion to soluble sugars during ripening. Little is known about the structure of major gene families involved in banana starch metabolism and their evolution compared to other species. To identify genes involved in banana starch metabolism and investigate their evolutionary history, we analyzed six gene families playing a crucial role in plant starch biosynthesis and degradation: the ADP-glucose pyrophosphorylases (AGPases), starch synthases (SS), starch branching enzymes (SBE), debranching enzymes (DBE), -amylases (AMY) and -amylases (BAM). Using comparative genomics and phylogenetic approaches, these genes were classified into families and sub-families and orthology relationships with functional genes in Eudicots and in grasses were identified. In addition to known ancestral duplications shaping starch metabolism gene families, independent evolution in banana and grasses also occurred through lineage-specific whole genome duplications for specific sub-families of AGPases, SS, SBE and BAM genes; and through gene-scale duplications for AMY genes. In particular, banana lineage duplications yielded a set of AGPases, SBE and BAM genes that were highly or specifically expressed in banana fruits. Gene expression analysis highlighted a complex transcriptional reprogramming of starch metabolism genes during ripening of banana fruits. A differential regulation of expression between banana gene duplicates was identified for SBE and BAM genes, suggesting that part of starch metabolism regulation in the fruit evolved in the banana lineage